2017
DOI: 10.5812/ijpbs.7832
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Health-Related Quality of Life, Depression, and Associated Factors Among Parents of Children with Autism in Kermanshah, Iran

Abstract: Background: The focus of recent research has significantly shifted from explaining the causes and symptoms of autism to investigating issues related to the parents of autistic children. Objectives: This study aimed to investigate health-related quality of life (HRQOL), depression, and associated factors among parents of autistic children in Kermanshah, Iran. Methods: In this cross sectional study performed in 2015, a total of 97 male and female parents of autistic children completed 3 questionnaires: backgroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…It is also found that if the IQ (Intelligence quotient) of the children decreases or is lower compared to other children' IQ depression in parents increases [21]. Another research with parents of autistic children found no significant gender differences in depression levels [23].…”
Section: Types Of Depressionmentioning
confidence: 99%
“…It is also found that if the IQ (Intelligence quotient) of the children decreases or is lower compared to other children' IQ depression in parents increases [21]. Another research with parents of autistic children found no significant gender differences in depression levels [23].…”
Section: Types Of Depressionmentioning
confidence: 99%
“…A total of 17 studies (18 records 123,[211][212][213][214][215][216][217][218][219][220][221][222][223][224][225][226] ) were identified reporting quality-of-life measures in carers and parents of children with autism or a related condition. The majority of the included studies were cross-sectional surveys, with the exception being a trial investigating a parent-targeted education programme.…”
Section: Studies Conducted In Carers and Parentsmentioning
confidence: 99%
“…221 All of the studies elicited values directly from the carer or parent. The most commonly used tool was the SF-36, used in 11 [214][215][216][217][218][219][220][221][222][223][224][225] of the 17 studies. A further three studies [211][212][213] reported WHOQOL-BREF, two studies 123,226 used EuroQol-5 Dimensions, one study 227 used the SF-12 and one study 123 used the SF-6D.…”
Section: Studies Conducted In Carers and Parentsmentioning
confidence: 99%